Functions of the opinion leader and he or she performs - Liepinytė-Kytrienė, Diana (Lietuvių kalba, 2015)
The aim of the article is to describe the functions of the opinion leader and he or she performs. The news portal „Delfi.lt“ articles from the year 2013, in which the most popular (according to the data of the survey company TNS LT) opinion leaders express their views serve as a basis in the article. Theoretical presumptions that their personal opinions shape the public opinion, affect social decisions and actions, are applied. Although the opinion leaders achieve popularity firstly through social activeness; however, for the purpose of persuasiveness an important role is attributed to linguistic peculiarities. In many cases, they determine the aspects the readers are to notice and remember. A person working towards becoming an opinion leader must meet the requirements of media channels, observe the general oratory requirements (language regularity, purity, clarity, simplicity, consistency, vividness, appropriateness, and aesthetic appeal), and fulfil the main functions of his or her text: to explain, prove, and persuade.
Keywords: opinion leader; performs; news portal; stilistics